Birth weight discordance, DNA methylation, and cortical morphology of adolescent monozygotic twins. Issue 4 (29th December 2016) - Casey, Kevin F.; Levesque, Melissa L.; Szyf, Moshe; Ismaylova, Elmira; Verner, Marie‐Pier; Suderman, Matthew; Vitaro, Frank; Brendgen, Mara; Dionne, Ginette; Boivin, Michel; Tremblay, Richard E.; Booij, Linda
Abstract: Background: Several studies have shown that the in utero environment, which can be indexed by birth weight (BW), is associated with cortical morphology in adolescence and adulthood. Work in monozygotic (MZ) twins suggests that this association is driven by non‐shared environmental factors. This correlation could be the result of in utero impacts on DNA methylation. The aim of the present study with MZ twins is to replicate the association between discordance in BW and brain morphology and test whether discordance in DNA methylation mediates this relationship. Methods: One hundred and four adolescent MZ twins (52 pairs, of which 42% were male pairs) who have been followed regularly since birth underwent T1 weighted structural MRI, and epigenome‐wide assessment of DNA methylation from saliva at age 15. Results: Co‐twins had very similar measures of DNA methylation and cortical morphology. Higher BW members of a twin pair had increased total cortical surface area, and decreased cortical thickness compared to their lower BW sibling. BW Discordance was positively associated with both cortical surface area and cortical volume discordance. Genes involved in neurodevelopment were tentatively identified as mediators of both the BW ‐ cortical volume, and BW‐ cortical surface area relationships. Conclusions: The association between BW and cortical morphology in adolescence appears to be attributable to in utero environmental effects, and DNA methylation may play a role in mediating this relationship. Hum Brain Mapp 38:2037–2050, 2017 . ©2017 Wiley Periodicals, Inc.